Model of Overlying Strata Structure in Large Mining Height Excavating Condition and Calculation of Support Working Resistance - Fengfeng Wu; Xin Yue; Jingxuan Yang; Beiju Du; Jian Zhang; Bo Lv (Geofluids)
Aiming at the wide range of rock strata movement and collapse, poor stability and high damage rate of the working face support and being prone to crushing of the support in large mining height face, analog simulation, theoretical analysis, and field measurements have been carried out to analyze roof breaking structure form and calculation method of support reasonable support resistance of large mining height face. The researches show that, affected by the space of the mined-out area, the roof of the large mining height working face will take on the structural form of “combined suspended beam-nonhinged roof-hinged roof”; the interaction system between the support and the surrounding rock consists of “hinged roof structure,” “nonhingeable roof structure,” “combined suspension beam structure,” and the support. The support resistance should adapt to the change of the overlying rock structure’s instability movement, bearing the weight of the structure itself and the additional load generated by the movement. Combining with the mining conditions of Jinhuagong Coal Mine’s large mining height face in Datong mining area, the reasonable support resistance of the working face support is analyzed. The mine pressure monitoring shows that the ZZ13000/28/60 type support and shield hydraulic support can meet the requirements of roof control; the research results ensure the safe mining of the large mining height face.